Bio-based and photocrosslinked electrospun antibacterial nanofibrous membranes for air filtration. (1st February 2019) - Zhu, Miaomiao; Xiong, Ranhua; Huang, Chaobo
Highlights: Fabrication of bio-based air filtration membranes via green electrospinning and UV cured. This Bio-based and versatile fibrous membranes possess excellent air filtration performance and antibacterial activity. These newly designed membranes can be applied in eco-friendly air filtration materials. Abstract: Air pollution is becoming more and more severe especially in developing countries. It is urgent to seek an effective protection for the unacceptable levels of the air pollution. Up to date, the air filtration is a widely used method to protect us from the air pollution. However, most of the air filtration membranes in fabrication process is required to use harmful organic solvents. Here, we report a human friendly, multifunctional and bio-based chitosan/poly (vinyl alcohol) air filtration membrane via green electrospinning and UV-cured. This green approach avoid use hazardous organic solvents which caused the residual solvents could bring the human subprime damage. Specifically, the superhydrophobic silica nanoparticles is introduced on the nanofibers to formation of the rough surface to increase filtration efficiency. In addition, the Ag nanoparticles (NPs) are fabricated on the surface through UV reduction of AgNO3 to achieve the aim of antibacterial treatment. The CS/PVA@SiO2 /Ag NPs membranes not only possess excellent filtration performance but efficiently antibacterial activities. As this green, multifunctional and bio-based CS/PVA@SiO2 /Ag NPs air filtration membranes have several superior features like high air filtration performance, biological compatibility and antibacterial, it has great potential application in eco-friendly air filtration materials, especially in personal air filtration materials.